A novel videoscope and tool kit for percutaneous pericardial access under direct visualization - Justin D. Opfermann; Jacqueline M. Contento; Paige N. Mass; Axel Krieger; Charles I. Berul; Rohan N. Kumthekar (BioMedical Engineering OnLine, 2023)
Abstract Background Pericardial access is necessary for the application of epicardial cardiac therapies including ablation catheters, pacing and defibrillation leads, and left atrial appendage closure systems. Pericardial access under fluoroscopic guidance is difficult in patients without pericardial effusions and may result in coronary artery damage, ventricular injury, or perforation with potentially life-threatening pericardial bleeding in up to 10% of cases. There is a clinical need for a pericardial access technique to safely deliver epicardial cardiac therapies. Methods In this paper, we describe the design and evaluation of a novel videoscope and tool kit to percutaneously access the pericardial space under direct visualization. Imaging is performed by a micro-CMOS camera with an automatic gain adjustment software to prevent image saturation. Imaging quality is quantified using known optical targets, while tool performance is evaluated in pediatric insufflation and pericardial access simulators. Device safety and efficacy is demonstrated by infant porcine preclinical studies (N = 6). Results The videoscope has a resolution of 400 × 400 pixels, imaging rate of 30 frames per second, and fits within the lumen of a 14G needle. The tool can resolve features smaller than 39.4 µm, achieves a magnification of 24x, and has a maximum of 3.5% distortion within the field of view. Successful pericardial access was achieved in pediatric simulators and acute in vivo animal studies. During in vivo testing, it took the electrophysiologist an average of 66.83 ± 32.86 s to insert the pericardial access tool into the thoracic space and visualize the heart. After visualizing the heart, it took an average of 136.67 ± 80.63 s to access the pericardial space under direct visualization. The total time to pericardial access measured from needle insertion was 6.7 × quicker than pericardial access using alternative direct visualization techniques. There was no incidence of ventricular perforation. Conclusions Percutaneous pericardial access under direct visualization is a promising technique to access the pericardial space without complications in simulated and in vivo animal models.